The Fairy-Tale Detectives - Buckley, Michael; Ferguson, Peter (New York : Scholastic, 2007)
Orphans Sabrina and Daphne Grimm are sent to live with an eccentric grandmother that they have always believed to be dead.
Keywords: children -- fiction